A new productivity index to measure economic sustainability of the mining industry (2010)
This document aims to introduce a total productivity index to measure the economic sustainability of the mining industry. This index will take into account any technical developments, means of use of productive factors (i.e. inefficiencies and scale effects) and the effects on the growth of the geological properties in the resources to be exploited (particularly the effects of resource reduction or reserves depletion). This new index will then be applied to the example of the Spanish mining industry, with some interesting findings regarding the configuration of sustainable mining policies.